Allelopathic effects of sunflower water extract integrated with affinity herbicide on weed control and wheat yield - Jatoi, Muhammad Tahir; Ahmed, Samreen Riaz; Lahori, Altaf Hussain; Sydorenko, Volodymyr; Afzal, Ambreen; Kandhro, Muhammad Nawaz; Janveri, Sarwat Haider; Jatio, Haider Bux; Jatoi, Zaheer Ahmed; Panhwar, Sajjad Ali; Pruskyi, Andrii (Ecological Questions, 2022)
The aim of present study was to investigate the allelopathic impact of sunflower water extract integrated with affinity herbicide on weed management and production of wheat variety TD-1 under field condition. The trial was carried out in a three replicated and the average plot size was kept at 3x5m (15 m2). The obtained data showed that the all the treatments considerably (P<0.05) minimized weed density, weed fresh weight, weed dry weight and weed control up to 90.33, 89.31, 89.61, 90.33% with application of sunflower water extract (1:10) @ 20 L ha-1 (One spray at 25 DAS) + Affinity 50 WP @ 0.75 kg ha-1 (One spray at 25 DAS) than control treatment. The application of sunflower water extract (1:10) @ 20 L ha-1 (One spray at 25 DAS) + Affinity 50 WP @ 0.75 kg ha-1 (One spray at 25 DAS) significantly increased number of tillers (32.34%), plant height (14.59%), spike length (27.89%), grains spike-1 (16.80%), grain weight plant-1 (47%), seed index (19.60%) and grain yield (51%) of wheat as compared with control. Overall results indicated that the sunflower water extract integrated with herbicide can be successfully used to control the narrow and broad leaves in wheat crop.